Changeable requirements & Answers With a dynamic system in order to continual improvement of the environmental performance of a rubber industrial big company - Péterné Baranyi, Rita (International Journal of Engineering and Management Sciences, 2019)
The topic of this article is the analysis of the changeable environmental requirements for the Environmental Management Systems (EMS) of the companies. The strengthened environmental criteria of the 21st century creates new challenges for the participants of the business sphere. In order to satisfy the criteria of the stakeholders, it is necessary to build out a - by the top management - preferred and proactive EMS that can contain also a life cycle thinking method. This logic is supported by the new ISO14001:2015 standard, too. In the first part of the article the stakeholder conception and the new standard model is presented based on literature analysis. The second part of the article presents an environmental management tool developed by a multinational, tyre company. The model combines the stakeholder conception, the requirements and the life cycle assessment (LCA) in order to respond to the new environmental management challenges. The last part of the article closes with the new development possibilities of the presented environmental management tool worked out by the author.